Physiological prion and activity of plasma membrane Na(+),K(+)- and Ca(2+)-ATPase in the medulla oblongata of rats of different ages - M. V. Kushkevych; V. V. Vlizlo; U. V. Martyn (The Ukrainian Biochemical Journal, 2013)
Based on the results of immunohistochemical analysis of the rat medulla tissue the localization of physiological prion has been established. Specifically, in rats aged one month they are placed in the gray matter near the bodies of neurons and mikrohliocytes and in animals of six and thirty months – in olive kernel core and upward path bodies. Physiological prion is localized along the nerve processes and is absent in the neuron bodies. In the medulla oblongata of animals aged six months its amount is the highest compared to animals of other age. The activity of plasma membrane ATPases in this tissue decreases with age, the content of sodium and calcium ions increases, while that of potassium is almost unchanged.